Crossbreeding cattle in beef production programmes in Kenya. I. Comparison of purebred Boran and Boran crossed with the Charolais, Ayrshire and Santa Gertrudis breeds - Gregory, K.E.; Trail, J.C.M.; Sandford, J.; Durkin, J.W. (Springer, 1984)
Presented data on maternal traits, i.e.Age at first calving, calving interval, calf weaning weight and cow productivity index, of pure Boran and Boran crossbred w. each of Charolais, Ayrshire and Santa Gertrudis on privately owned ranches in Machakos District, Kenya.